Onabotulinumtoxin A (Botox): A reasonable alternative for refractory neurogenic bladder dysfunction in children and young adults. Issue 8 (6th September 2021) - Softness, Kenneth A.; Thaker, Hatim; Theva, Didi; Rajender, Archana; Cilento, Bartley G.; Bauer, Stuart B.
Abstract: Aims: We aimed to describe the effectiveness of Onabotulinumtoxin A (Botox) in children with neurogenic bladder (NGB) unresponsive to medical therapy to determine urodynamic parameters predictive of success. Methods: Children receiving Botox for refractory NGB, between 2008 and 2019, from a single academic center, were included in this study. Botox success was defined as improvement of incontinence and/or urodynamic parameters. Results: Of 34 patients who received Botox, 13 (38.2%) had a positive response from their first injection, with improvement in capacity by a median of 35% of expected capacity for age compared to only a 9% increase in those who did not respond clinically. When patients were divided into groups by baseline urodynamic parameters, high‐pressure (Pdetmax > 20 cm H2 O) patients had significantly greater improvement in compliance compared with low‐pressure patients ( p = 0.017). Low compliance patients (<10 ml/cm H2 O) had a dramatic improvement of 3.08 ml/cm H2 O in their compliance compared with minimal change in the high compliance group ( p = 0.003). Finally, low‐capacity (<50% of expected CC) patients had significant improvement in capacity and compliance when compared with high‐capacity patients ( p = 0.004 and p = 0.036, respectively). Improvement in detrusor overactivity (DO) was noted in both the clinical responders and non‐responders. Conclusion: In our series, 38% had clinical success with intradetrusor Botox injections for refractory neurogenic bladder. When successful, improvement in capacity and compliance, DO, and/or incontinence was consistent with prior literature. While we could not determine which parameters predicted success, subdividing patients into categories based on baseline urodynamic parameters identified who would benefit from Botox treatment based on differential improvements in capacity and compliance. At least 1 injection of Botox should be considered for a subset of children with refractory NGB, before undertaking more invasive treatments.